Algorithmic echo chamber as a challenge of Digital citizenship in discourse polarization On tiktok social media - Ridha, Muhammad Kamil; Mulyono, Budi; Yulianto, Edi Mustofa (Universitas Tanjungpura, 2025)
The digital era, especially through platforms like TikTok, has transformed the landscape of public discourse among Indonesia's youth. This research investigates the mechanisms of polarization in the viral socio-cultural trend 'Kabur Aja Dulu' on TikTok, aiming to uncover how algorithmic echo chambers are formed and their impact on digital civic engagement. Utilizing a convergent mixed-methods design, this study combines quantitative analysis of 60 TikTok videos (30 Pro, 30 Contra) with qualitative discourse analysis. The quantitative analysis uses MANOVA to compare user engagement profiles (likes, comments, shares), while the qualitative analysis examines the framing strategies of both sides. Statistical results show that Pro sentiment content significantly achieves higher engagement levels across all metrics (Pillai's Trace = 0.373, p < 0.001) compared to Contra content. Qualitative findings reveal that the Pro camp successfully utilized emotional and aspirational framing (healing, self-care), which resonates more with TikTok's algorithm logic. Conversely, the Contra camp employed normative-critical framing (nationalism, privilege) which is less effective in triggering engagement. It is concluded that polarization is reinforced by algorithmic curation that amplifies affirmative discourse and validates emotions, thus pushing the shift in digital civic practices towards a more therapeutic and individualistic direction, while hindering deliberative public dialogue